Is binge drinking in young adults associated with an alcohol-specific impairment of response inhibition? - Czapla, Marta; Simon, Joe J.; Friederich, Hans-Christoph; Herpertz, Sabine (European addiction research, 2015)
Background/Aims: Little is known about the association of binge drinking with impulsivity related to trait- or state-like aspects of behavior. The aim of the present study was therefore to investigate whether binge drinkers show an impairment of inhibitory control in comparison to non-binge drinkers when confronted with alcohol-associated or control stimuli, and whether this is reflected in self-reported impulsivity. Methods: A go/no-go task with pictures of alcoholic and nonalcoholic beverages as well as control stimuli was administered to binge drinkers and a gender-matched group of non-binge drinkers. All participants also completed the Barratt Impulsiveness Scale (BIS-11). Results: We found an alcohol-specific impairment of response inhibition for binge drinkers only, while the groups did not differ with regard to overall response inhibition to the experimental stimuli or self-reported impulsiveness (BIS-11). In addition, the number of commission errors in response to alcohol-associated stimuli was the only significant predictor of binge drinking. Conclusion: The findings of the present study suggest that when young adults have established binge drinking as a common drinking pattern, impairment of inhibition in response to alcoholic stimuli is the only significant predictor of binge drinking, but not general impulsive behavior.